Glycosidase Inhibitors as Potential HIV Entry Inhibitors? - Robina, I.; Moreno-Vargas, A.J.; Carmona, A.T.; Vogel, P.
A few a-L-fucosidase inhibitors and a-D-glucosidase inhibitors have shown in vitro anti-HIV activities, that have been attributed to their ability to inhibit HIV entry. The mechanism of action of inhibitors such as 1- deoxynojirimycin (1)is not clearly established. One possible hypothesis is that the glycosidase inhibition affects the final conformation of the glycoproteins involved in the virus/cell recognition and fusion phenomena. This hypothesis is presented critically and the mechanisms of some glycoprotein biosynthesis are out-lined. Up to now, very few glycosidase inhibitors have been assayed for their potential as HIV entry inhibitors. Further assaying should be done and larger collections of glycosidase inhibitors should be prepared. To help investigations in that perspective, the inhibitory activities of a-glucosidase and a-L-fucosidase inhibitors have been summarize
Keywords: GLYCOPROTEIN; A-D-GLUCOSIDASE INHIBITORS; A-L-FUCOSIDASE INHIBITORS; 1-DEOXYNOJIRIMYCIN; GLYCOCONJUGATES; NGLYCANS; O-GLYCANS; GLYCOLIPIDS; PROTEIN FOLDING